AN ENHANCED HYBRID PARETO METAHEURITIC ALGORITHM-BASED MULTICAST TREE ESTIMATION FOR RELIABLE MULTICAST ROUTING IN VANETS - Janakiraman, Sengathir (APTIKOM Journal on Computer Science and Information Technologies, 2018)
Prompt and reliable data dissemination among the vehicular nodes of the network is indispensable as itsmobility rate and limited coverage characteristics introduce the possibility of frequent topology changes. The effectiveand efficient sharing of critical information in the event of emergency necessitates either direct interaction or RoadSide Units (RSUs)-based vehicular communication in the primitive place. Multicast routing is confirmed to be thesignificant scheme of data transfer since they establish reliable data dissemination between the source and destinationvehicular nodes by estimating an optimal multicast tree. Moreover, QoS-constraint enforced meta-heuristic approachesare considered to be excellent for determining optimal multicast tree under multicasting. An Enhanced Hybrid ParetoMetaheuritic Algorithm-based Multicast Tree Estimation Scheme (EHPMA-MTES) is contributed for reliable multicastrouting. The proposed EHPMA-MTES is confirmed to reduce the cost of transmission by 28% through the minimizationof the multicast tree count formed during the process of multicast routing.